The Saharan heat low and moisture transport pathways in the central Sahara—Multiaircraft observations and Africa‐LAM evaluation. Issue 10 (18th May 2015) - Engelstaedter, S.; Washington, R.; Flamant, C.; Parker, D. J.; Allen, C. J. T.; Todd, M. C.
Abstract We present a characterization of the Saharan heat low (SHL) based on dropsonde observations made on 22 June 2011 by two simultaneously flying aircraft during the Fennec project. The observations are used to identify moisture transport pathways and to validate the UK Met Office limited area model for northern Africa (Africa‐LAM). The observations capture the SHL, harmattan, and monsoon surge. The SHL has a northeast‐southwest orientated elongated shape centered over northern Mauritania. The SHL core is associated with a 950 hPa temperature minimum (36.4°C) in the morning caused by the monsoon surge and a maximum (42.6°C) in the afternoon. The monsoon surge east of the SHL core splits into two transport pathways: (a) curving around the SHL core in the north, especially pronounced in a morning near‐surface layer, and (b) northeastward transport within the ~2 km deep monsoon surge (afternoon observations only). In the morning the model forecasts the harmattan, monsoon surge, and the SHL geographic location and northeast‐southwest orientation well but the model represents the SHL flatter and more spatially extended and overestimates the convective boundary layer (CBL) by up to ~0.3 km. The simulated afternoon SHL location appears shifted westward by up to ~1°. The model overestimates the shallow afternoon monsoon surge CBL depth of ~1.8 km by >2 km resulting in southwestward transport of vertically mixed moisture above ~2.5 km contrasting observed northeastward‐only transport at lower levels. This moisture distribution model error is likely to have consequences for simulations of Saharan thermodynamics and dust emissions caused by convection‐driven cold pools.